Eleven unforgettable travellers to Kashmir - Mota, Avtar (Jammu Avtar Mota, 2024)
The book gives fascinating details of eleven visitors to the Kashmir valley who were the most influential personalities from the fields of literature, archaeology, social service, cinema, modern healthcare, modern education, etc. The personalities included are Gandhi Ji, Vinoba Bhave Tagore, Swami Vivekananda, Firaq Gorakhpuri, Dilip Kumar, David Lean, V S Naipaul, Cecil Tyndale Biscoe, Aurel Stein and Neve Brothers ( the doctors who brought modern allopathic medicine and surgery to Kashmir ). Every chapter is full of historical anecdotes and rare information about their stay and activities. The book is a treasure trove of information about Kashmir . Anything that one wants to know about Kashmir in the 20th century is available in the chapters of this book.
Keywords: Travellers of Kashmir; Travelogue